SENSEI: Characterization of Single-Electron Events Using a Skipper Charge-Coupled Device - Barak, Liron; Bloch, Itay M.; Botti, Ana Martina; Cababie, Mariano Ruben; Cancelo, Gustavo Indalecio; Chaplinsky, Luke; Chierchie, Fernando; Crisler, Michael; Drlica Wagner, Alex; Essig, Rouven; Estrada, Juan; Etzion, Erez; et al. (American Physical Society, 2022)
Fil: Barak, Liron. Universitat Tel Aviv; Israel